RESPIRATORY MUSCLE TRAINING WITH THERABAND VERSUS INCENTIVE SPIROMETER AMONG INDIVIDUALS WITH BRONCHIAL ASTHMA - REKHA, K.; DOSS, D. SAMUEL SUNDAR; SIDDIUE, MOHAMMED ABUBAKKER (International Journal of Current Pharmaceutical Research, 2020)
Objective: To determine and compare the effects of Theraband exercises with Incentive Spirometer exercise in improving respiratory muscle strength among bronchial asthma. Methods: In this study, 30 Individuals with Bronchial asthma were taken and assessed for FEV1/FVC, Maximum voluntary ventilation (MVV) using a computerized spirometer, dyspnea level graded using MMRC scale and diaphragm muscle strength assessed using manual muscle testing (MMT) as pre-test then the individuals were randomly allocated in two groups: Group A and Group B. Group A (n=15) received Theraband exercise and Group B (n=15) were treated with incentive spirometer for a total period of 4 w following which the outcome measures were repeated for post-test. Results: Based on the obtained statistics, both the groups showed significant improvement within groups when comparing pre and post-test measures. On comparing the mean values of the post-test between the groups, theraband exercises showed clinically higher significant results than incentive spirometer exercises. Conclusion: From the result, it shall been concluded that both theraband exercises and incentive spirometer exercises shows improvement in MVV, FEV1/FVC, reduced dyspnea and increased respiratory muscle strength. Hence, theraband exercises are effective compared to the incentive spirometer.